2015
DOI: 10.1002/cbic.201500519
|View full text |Cite
|
Sign up to set email alerts
|

Furospinosulin‐1, Marine Spongean Furanosesterterpene, Suppresses the Growth of Hypoxia‐Adapted Cancer Cells by Binding to Transcriptional Regulators p54nrb and LEDGF/p75

Abstract: Hypoxia-adapted cancer cells in tumors contribute to the pathological progression of cancer. Cancer research has therefore focused on the identification of molecules responsible for hypoxia adaptation in cancer cells, as well as the development of new compounds with action against hypoxia-adapted cancer cells. The marine natural product furospinosulin-1 (1) has displayed hypoxia-selective growth inhibition against cultured cancer cells, and has shown in vivo anti-tumor activity, although its precise mode of ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 40 publications
(88 reference statements)
0
13
0
Order By: Relevance
“…The electrospray ionization time-of-flight mass spectrometry (ESI-TOF MS) of 1 showed a quasi-molecular ion peak [M+Na] + at m/z 381, and the molecular formula was determined as C 23 6 Hz, H-4) and 7.21 (dd, J=7.6 and 4.9 Hz, H-5); δ C 149.7 (C-2), 147.0 (C-6), 138.0 (C-3), 135.9 (C-4) and 123.3 (C-5)] suggested the presence of 3-alkylpyridine unit ( Table 1). The UV absorption maximum at 260 nm also implied the presence of pyridine chromophore.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The electrospray ionization time-of-flight mass spectrometry (ESI-TOF MS) of 1 showed a quasi-molecular ion peak [M+Na] + at m/z 381, and the molecular formula was determined as C 23 6 Hz, H-4) and 7.21 (dd, J=7.6 and 4.9 Hz, H-5); δ C 149.7 (C-2), 147.0 (C-6), 138.0 (C-3), 135.9 (C-4) and 123.3 (C-5)] suggested the presence of 3-alkylpyridine unit ( Table 1). The UV absorption maximum at 260 nm also implied the presence of pyridine chromophore.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, we have shown the validity of these compounds as new drug leads, through the analytical studies of target molecules and the structureactivity relationships (SAR) studies using the synthesized analogue compounds. [6][7][8] From the recent biological studies of the cancer cells adapted to the nutrient starvation, the activation of phosphoinositide 3-kinase (PI3k)/v-akt murine thymoma viral oncogene homolog 1 (Akt)/mammalian target of rapamycin (mTOR) signaling pathway and the unfolded protein response (UPR) such as induction of glucose-related protein 78 (GRP78) were found to be important for the adaptation of cancer cells to nutrient starvation, and these processes have attracted attention as drug targets for cancer chemotherapy. 9,10) Kigamicin D, a polycyclic xanthone isolated from the culture broth of Amycolatopsis sp., inhibited activation of Akt signaling and showed selective cytotoxic activity against pancreatic cancer cells under the condition of nutrient starvation compared with general culture conditions.…”
mentioning
confidence: 99%
“…Furospinosulin-1 has been shown to cause hypoxia-selective growth inhibition in cultured cancer cells and exhibits in vivo antitumor effects. A target identification study revealed that furospinosulin-1 directly binds to the transcriptional regulators p54 nrb and lens epithelium-derived growth factor/p75 [10]. In addition, further investigations of the constituents of D. elegans extracts inducing hypoxia-selective growth inhibition have led to the isolation of sesquiterpene phenol dictyoceratin-C ( 2 ) as an active substance and have demonstrated that dictyoceratin-A ( 1 ) shows similar biological activity [11].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, some natural products have been reported to exert selective inhibition against cancer cells that have adapted to hypoxic or nutrient-starved conditions; for example, furospinosulin-1 (furanosesterterpene) and dictyoceratins A and C (sesquiterpene phenols) isolated from the marine sponge, Dactylospongia elegans, selectively inhibit the growth of hypoxiaadapted human prostate cancer DU145 cells. 4,5 Kigamicin D (polycyclic xanthone) and ancistrolikokine E3 (naphthylisoquinoline alkaloid) isolated from the culture extract of Amycolatopsis sp. and the plant Ancistrocladus likoko, respectively, showed selective cytotoxic activity on the nutrient-starved PANC-1 cells.…”
mentioning
confidence: 99%